The Role of Value Creation Innovation in Mediating the Relationship Between Digital Transformation, Strategic Agility, and Organizational Performance - Marsanto Adi Nurcahyo; Asep Hermawan; Sarfilianty Anggiani (International Journal of Business, Economics, and Social Development, 2025)
The objectives of this study are to examine the mediating role of value creation innovation in the relationship between organizational performance and the independent variables digital transformation and strategic agility. This study employs a quantitative research method with a nonprobability sampling approach and purposive sampling technique, targeting first-level and middle-level managers as the unit of analysis. The final sample consists of 156 respondents with data collected cross-sectionally. The collected data were analyzed using SmartPLS version 4. The results indicate that value creation innovation plays a full mediating role in the relationship between digital transformation and strategic agility on organizational performance, as the estimated mediation effect is greater than the direct effect. Theoretical implications of this research highlight that incorporating value creation innovation as a mediating variable strengthens the impact of digital transformation and strategic agility on organizational performance. The limitations of this study are that the respondents are only companies in bonded zones whose numbers are limited, with variables and research methods that are still limited. Future research should consider expanding the sample to include companies beyond bonded zones, integrating additional exogenous variables into the research model, and employing qualitative or mixed methods approaches to gain deeper insights.